Moment of Citizenship: Association and Aspiration of Minahasan, North Sulawesi - Amin, Basri (Universitas Negeri Semarang, 2017)
This article is about Minahasa, an ethnic group in North Sulawesi, Indonesia. This article analyzes the dynamics of Minahasan collective actions in early 2000 in responding to the sectarian debates throughout the Indonesian archipelago where the issues of religion and ethnicity are flourishing. I draw on case studies from Kongres Minahasa Raya (the Great Congress of Minahasan) as entry point to explore the ways Minahasans have been peacefully demanding serious attention to and clarification on constitutionally-based provisions of citizenship in Indonesia. It is my hope that this article will show how such “collective strategies” are created and maintained by Minahasans. This is an example of an ongoing feature of how citizens’ arenas and rights are contested in contemporary Indonesia.